A symmetric anchor designed barbed suture versus conventional interrupted sutures in total knee arthroplasty: A multicenter, randomized controlled trial. (2nd December 2020) - Wang, Wei; Yan, Shigui; Liu, Feng; Chai, Wei; Zuo, Jianlin; Xiao, Jun; Niels-Derrek, Schmitz; Zhu, Qing; Sanghita, Bhattacharya; Bogdan, Ilie; Wang, Kunzheng
Objective: This randomized controlled study was designed to compare the wound closure efficacy and safety of barbed suture in comparison to the conventional interrupted suture for total knee arthroplasty (TKA). Methods: This multicenter, single-blind, randomized controlled trial enrolled 184 patients who underwent elective TKA between June 2017 and April 2018. The subjects were randomized between two groups. Surgical incision closure time was considered as the primary end point. Results: A total of 184 patients participated in this randomized controlled trial; 91 patients had wound closure that involved barbed suture and 93 patients underwent conventional treatment—that is interrupted suturing with nonbarbed sutures. The surgical incision closure time was shorter ( p < 0.0001) in the barbed suture group compared with the control group (15.5 ± 4.88 vs. 20.9 ± 6.30 min). However, both groups were found to be equal in terms of the rate of postoperative complications. Conclusion: Usage of the symmetric anchor designed barbed suture is safe, efficacious, and demonstrates a decrease in surgical incision closure time in patients undergoing TKA compared to interrupted closure using conventional sutures. Future studies are warranted to demonstrate clinical and economic benefits of barbed sutures.